PERCEIVED STRESS PREDICTS FUNCTION AND MOVEMENT-EVOKED JOINT PAIN IN AGING AFRICAN AMERICANS WITH OSTEOARTHRITIS. (11th November 2018) - Booker, S; Josue, C; Terry, E; Sibille, K; Cruz-Almeida, Y; Bradley, L; Goodin, B; Fillingim, R
Abstract: Older non-Hispanic African Americans (NHAAs) experience greater clinical and experimental pain sensitivity, arthritis-attributable physical limitations, and disability. A few studies show that NHAAs with functional limitations exhibit low perceived arthritis stress but high life stressors. Some postulate that chronic biopsychosocial stress may be one mechanism explaining greater pain sensitivity and aging in NHAAs. However, no study has examined the association between perceived life stress and experimental measures of function and pain in older NHAAs. We aimed to identify how stress impacts function/mobility and subsequent movement-evoked joint pain. This secondary data analysis of an observational cohort study included 82 NHAAs with knee pain from Alabama and Florida who were 58 years on average (range: 50–73 years) with low-middle income. Measures included: Perceived Stress Scale, Short Physical Performance Battery (SPPB; measures gait speed, balance, and chair standing; total score range: 0 worst performance to 12 best performance), pain intensity (0 no pain to 100 worst pain), and demographics. Controlling for age, study site, gender, BMI, education and income, GLM regression indicated that perceived stress statistically predicts (p= 0.036) overall function. NHAAs with high perceived stress scored lower on the SPPB (mean= 8.33) than moderate stress (mean= 8.48) and low stress (mean= 9.74). For all three SPPB functional tasks, perceived stress was a significant predictor of movement-evoked pain, with high stress predicting high pain intensity (average range: 50–86/100). Attenuating perceived chronic life stress may improve physical function and reduce joint pain, but more importantly allow NHAAs to live longer more purposeful mobile lives.